Systematic methodology for the preliminary design of future rotary VTOL martian aerobots - Youhanna, Vishal; Felicetti, Leonard; Ignatyev, Dmitry (Elsevier, 2025)
This paper proposes and describes a methodology for the preliminary design of aerobots for future Martian exploration missions within a framework. The methodology takes into account inputs derived from top-level mission requirements and site locations to obtain the critical mission parameters that affect the performance of the rotorcraft. The proposed methodology allows for incorporating multi-rotor configurations into the trade-offs based on the required power to perform flight profiles. The equations, based on momentum theory for conventional helicopters, are derived and generalised to estimate the required power for flight segments such as hover, vertical climb, and forward flight for rotorcraft with both overlapping and non-overlapping rotors such as coaxial, tandem, and multirotor configurations. The resulting performance data is used for sizing and selecting the critical components of the aerobot in a mission scenario, such as rotor and battery sizes. Notably, the analyses conducted on rotorcraft with single and dual rotors identified a tandem rotorcraft configuration without folding mechanisms as the optimal choice due to its superior power efficiency and mechanical simplicity. Through calculated equations for battery mass and available empty mass estimation, this framework enables the optimisation and selection of an efficient rotary VTOL aerobot for Martian missions in the years to come.
Keywords: 40 Engineering; 4001 Aerospace Engineering; Aerospace & Aeronautics; Mars exploration; Martian drone framework; Planetary aerobots; Rotorcraft conceptual design; UAV